2015
DOI: 10.1039/c5ta00299k
|View full text |Cite
|
Sign up to set email alerts
|

Cotton derived carbonaceous aerogels for the efficient removal of organic pollutants and heavy metal ions

Abstract: Carbon aerogels were made from waste cotton for the efficient removal of pollutants from aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
102
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(106 citation statements)
references
References 36 publications
2
102
0
2
Order By: Relevance
“…This result is in accordance with our previous studies, i.e., adsorption of metal cations is mainly contributed to the ion-exchange with interlayered Na + 30. 532 and 530 eV presents the O from adsorbed surface hydroxyl groups (-OH) and the crystal lattice [Ti-O 6 ] 54. In the high resolution O 1s spectra, the peak at ca.…”
supporting
confidence: 92%
“…This result is in accordance with our previous studies, i.e., adsorption of metal cations is mainly contributed to the ion-exchange with interlayered Na + 30. 532 and 530 eV presents the O from adsorbed surface hydroxyl groups (-OH) and the crystal lattice [Ti-O 6 ] 54. In the high resolution O 1s spectra, the peak at ca.…”
supporting
confidence: 92%
“…[34][35][36] More recently, researchers have made tremendous efforts to produce various porous carbons from inexpensive renewable biomasses such as bagasse, 37 cotton, 38 rice, 39 silk proteins, 40 lignosulphonatecellulose, 41 typha orientalis, 42 wood. 43 However, limited methods to access HPCs from biomass have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] PDA and its hybrid nanomaterials have been developed as novel adsorbents to remove organic dyes, such as PDA microspheres, 19 PDA-graphene composites or hydrogel, [20][21][22] Fe 3 O 4 -PDA core-shell microspheres, [23][24][25][26] CaCO 3 -PDA hybrids, 27 electrospun nanofibrous-PDA membranes, 28 and clay-PDA complexes. [34][35][36] Recently, Jin et al demonstrated that PDA-GO composite could adsorb dyes selectively. These drawbacks greatly limit the practical applications of PDA based adsorbents.…”
Section: Introductionmentioning
confidence: 99%